2007
DOI: 10.1021/ja074413c
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Oxidation of Hydrazo Derivatives Promoted by a TiCl3/HBr System

Abstract: Through a novel catalytic process of general synthetic interest, hydrazo compounds were efficiently and selectively converted into corresponding azo derivatives. The proposed mechanism of this process comprises two separate and distinctive catalytic cycles, linked together by radical species. The first cycle includes formation of a hydroxy radical, generated by Ti(III) single-electron reduction of H2O2. In the second cycle, the hydroxy radical oxidizes HBr into hypobromous acid, which in turn is reduced back t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(19 citation statements)
references
References 25 publications
(14 reference statements)
0
19
0
Order By: Relevance
“…Among the reported methods for the preparation of azo compounds, [85][86][87][88][89][90][91][92] this method has been found to be the most suitable. [93] We then focused our attention to study whether these azo compounds could be employed for the oxidative coupling of thiols to generate symmetrical disulfides.…”
Section: Resultsmentioning
confidence: 99%
“…Among the reported methods for the preparation of azo compounds, [85][86][87][88][89][90][91][92] this method has been found to be the most suitable. [93] We then focused our attention to study whether these azo compounds could be employed for the oxidative coupling of thiols to generate symmetrical disulfides.…”
Section: Resultsmentioning
confidence: 99%
“…Utilizing either O 2 or H 2 O 2 as an oxidant, NH 4 VO 3 , a Co II complex, CuCl 2 , TiCl 3 / HBr, Pd(OAc) 2 , a carbon nanotube-rhodium nanohybrid system, and reduced graphene oxide are able to catalyze this transformation. [6] Additionally, with KClO 3 /H 2 SO 4 as an oxidant, a catalytic amount of FeSO 4 is also feasible for this reaction. [7] Nevertheless, many methods suffer from long reaction times, special catalysts, and relatively tedious posttreatment.…”
mentioning
confidence: 99%
“…In this context, Gozin and coworkers previously reported the oxidative dehydrogenation reaction using H 2 O 2 as an external oxidant. 19 Moreover, the oxidative dehydrogenation reactions of different hydrazobenzenes were further investigated with 5 wt% Ni-Fe@N-doped-C catalyst under optimal conditions and the obtained data are listed in Table 4. It was found that all the electron-donating or electron-withdrawing group-bearing hydrazobenzenes could be efficiently transformed to azobenzenes with excellent selectivity and yields (entries 1-6).…”
Section: Properties Of the Ni-m@n-doped-c Catalystsmentioning
confidence: 99%
“…18 Therefore, it is important to precisely optimize the synergistically active metal sites and N-doped porous structures simultaneously over carbon-based catalysts for better exposure in dehydrogenation reactions. [19][20][21] In 2010, Titirici and coworkers described the hydrothermal treatment of chitosan, followed by calcination, for the preparation of carbonaceous materials. 22 Later, it was shown that chitosan could serve as an excellent precursor to generate Ndoped graphene.…”
Section: Introductionmentioning
confidence: 99%